2020
DOI: 10.1101/2020.12.21.423721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 Spike protein disrupts human cardiac pericytes function through CD147-receptor-mediated signalling: a potential non-infective mechanism of COVID-19 microvascular disease

Abstract: BackgroundSevere coronavirus disease 2019 (COVID-19) manifests as a life-threatening microvascular syndrome. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses primarily the capsid spike (S) protein to engage with its receptors and infect host cells. To date, it is still not known if the S protein alone, without the other viral elements, is able to trigger vascular cell signalling and provoke cell dysfunction.MethodsWe investigated the effects of the recombinant, stabilised S protein on prim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 61 publications
0
29
0
3
Order By: Relevance
“…Our study reveals the capacity and mechanism by which SARS-CoV-2 S mediates barrier dysfunction in epithelial and endothelial cells in vitro and vascular leak in vivo, thus suggesting that S alone can mediate barrier dysfunction independently from viral infection (33). Our work indicates that levels of S observed in clinical samples from COVID-19 patients are sufficient to mediate barrier dysfunction (250 ng/ml) (54,55). Our findings suggest a contribution of integrins to COVID-19 pathology, in addition to functioning in S-mediated viral entry (18,56).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our study reveals the capacity and mechanism by which SARS-CoV-2 S mediates barrier dysfunction in epithelial and endothelial cells in vitro and vascular leak in vivo, thus suggesting that S alone can mediate barrier dysfunction independently from viral infection (33). Our work indicates that levels of S observed in clinical samples from COVID-19 patients are sufficient to mediate barrier dysfunction (250 ng/ml) (54,55). Our findings suggest a contribution of integrins to COVID-19 pathology, in addition to functioning in S-mediated viral entry (18,56).…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, although we observe significant vascular leak in mice administered S, they do not overtly display signs of morbidity. Importantly, our findings suggest that the amounts of S circulating in patients following COVID vaccination (pg/mL levels) are too low to trigger vascular leak given that our phenotype requires ng-µg/mL levels that mimic the levels observed during severe COVID-19 cases (54,55). Taken together, our study and available literature (63) indicate that S-mediated vascular leak would not result from COVID-19 vaccination and therefore it is not correlated with vaccine adverse events.…”
Section: Discussionmentioning
confidence: 82%
“…SP may also interact with CD147 (EMMPRIN (extracellular matrix metalloprotease inducer)) in its invasion and dissemination processes [24]. The role of CD147 on SARS-CoV-2 spike protein-mediated disruption of cardiac pericyteendothelial cells has been reported [25]. Also, CoV attachment to oligosaccharide receptors via sialic acid contributes to viral entry into host cells [26].…”
Section: Sars-cov-2 and Covid-19mentioning
confidence: 99%
“…Hyperglycemia, as seen in diabetes, is associated with increased MMP activity [238]. Recently, it was shown that recombinant SP of SARS-CoV-2 interact with CD147 to disrupt the function of cardiac pericyte-endothelial cells [25]. Thus, MMP9 could be targeted as a possible additional therapy for COVID-19 (Fig.…”
Section: Co-morbidities Increase Risk Of Death From Covid-19: Outlinedmentioning
confidence: 99%
“…We presented in vitro evidence that the S protein alone can elicit functional alterations in pericytes from the human heart, reducing their angiogenic activity and inducing the secretion of pro-inflammatory and -apoptotic factors. These adverse phenomena could be mediated by the S protein interaction with CD147, as neutralization of this receptor by a blocking Ab prevented them [70]. Therefore, the use of receptor entry blocker may exert multiple benefits, reducing the intracellular viral load, viral replication and dampening early inflammatory response.…”
Section: Inhibition Of the Virus Entry Receptors Processing Protease And Downstream Mechanismsmentioning
confidence: 99%